Semipinacol and protoadamantane-adamantane rearrangements of 5, 6-dibromoadamantan-2-one and -2-ol. Issue 20 (18th May 2017) - Wang, Xiaofang; Dong, Yuxiang; Ezell, Edward L.; Garrison, Jered C.; Wood, James K.; Hagen, James P.; Vennerstrom, Jonathan L.
Abstract: A number of new polybrominated adamantanes were formed by rearrangements and bromination of 2, 2, 6, 6-tetrabromoadamantane under Friedel-Crafts conditions. Protoadamantane-4, 10-dione, 10-acetoxyprotoadamantan-4-one, 1, 2, 6-triacetoxyadamantane and 5, 6-diacetoxyadamantan-2-one were formed by successive semipinacol and protoadamantane-adamantane rearrangements of 5, 6-dibromoadamantan-2-one and 5, 6-dibromoadamantan-2-ol. This work may open up new pathways for the synthesis of 1, 2, 6-trisubstituted adamantanes. Graphical abstract: